(untitled) (Al-Academy, 2017)
This research studies the possibility of producing Bone China with available local and geological substitutes and other manufactured ones since it’s traditionally produced by Bone ash, Cornish stone, and China clay, while the substitutes are Kaolin instead of China clay and Feldspar potash instead of Cornish stone. Because of the unavailability of Feldspar in Iraq, it was substituted with the manufactured alternative Feldspar. Bone ash was prepared from cow bones with heating treatments, grinding and sifting. The alternative Feldspar was prepared by chemical analysis of the natural Feldspar potash with local materials that include Dwaikhla Kaolin, Urdhuma Silica sand, Potassium Carbonate, and Sodium Carbonate. The mixture was burned at (1250c○) before it was grinded. The mixture’s materials were sifted at (63µm). The samples were formed with slip casting by gypsum mold with a cut cone shape at (2×3×6 cm) to build a thickness of (3mm). The study materials consisted of two groups: Group 1 (BC.K.F) including Bone ash, Dwaikhla Kaolin, and the natural Feldspar, while Group 2 (BC.K.FR) had Bone ash, Dwaikhla Kaolin, and the manufactured alternative Feldspar. Every group included 8 recipes with the same percentages. The two groups were burned at (1220-1260c○), then tests were conducted: Chemical analyses, the outer appearance and color then the laboratory tests: the outer appearance, linear shrinkage, apparent porosity, water absorption, bulk density, hardness, scratching resistance, mineral analysis (XRD), color analyses, optical transmittance. After discussing and analyzing the results, it was concluded that the traditional materials substitutes gave matching and correspondent properties and specification of Bone China ceramic